Diaspora, identity, and store signs. Issue 3 (3rd July 2019) - Khayambashi, Shirin
Abstract : Public displays of cultural icons and images characterise community development. This research assesses the significance of public location in developing an ethnic community by problematising the tendencies of diasporic communities to display their respective cultural and communal identities conspicuously to claim a sense of neighbourhood and rejuvenate their ethnic, social capital. Each cultural image is applied to preserve the community's cultural norms and values, as well as represent the produced cultural hybridity in diaspora. For the purpose of this research, tactical depictions and representations of images, banners and advertisements in an Iranian Plaza, and the development of a diasporic marketplace is subjected to investigation and analysis. Through this investigation and exploration of the Persian diasporic community in Toronto, this paper argues for the importance of cultural signs and images in possessing a public location, which establishes strong community bonds and social capital in the host nation. The Public representation of culture, however, can be segregating and ghettoising an ethnic community from others. For collecting data, I immersed myself into an Iranian Plaza. As part of data collection, I collected images to further my research process via tangible and recordable data. Cultural images and symbols communicate certain values and characteristics to both the ethnic community and the general host population. Through the public display of images, the Persian community establishes a community, and distinguishes its ethnic group from other ethnic minorities and the dominant culture.